Analisis Peran Pancasila dalam Menanamkan Nilai-Nilai Luhur Kehidupan Berbangsa dan Bernegara - Handayani, Nur Fitri; Venna Puspita Sari; Wingkolatin Wingkolatin (International Forum of Researchers and Lecturers, 2026)
The moral crisis faced by the Indonesian nation is a serious challenge that can threaten the integrity and sustainability of the country's future. Phenomena such as corruption, intolerance, and weakening social integrity are clear evidence of the declining implementation of the noble values ​​contained in Pancasila. Pancasila Education has a strategic position in building national character and instilling moral values, especially in the younger generation. This article aims to examine the moral crisis in Indonesia and analyze the role of Pancasila Education in providing solutions to these problems. This study uses a literature research method to assess the relevance of Pancasila values ​​and the effectiveness of the implementation of Pancasila Education. The study results show that Pancasila values ​​such as religiosity, humanity, unity, democracy, and social justice have great potential in forming moral individuals. However, there are various challenges, including low student interest, lack of innovation in teaching, and the influence of globalization that can hinder the optimization of Pancasila Education. To overcome these obstacles, strategic steps are needed such as strengthening the curriculum, improving the quality of educators, and collaboration between families, schools, and the community. With maximum implementation, Pancasila Education can be the main key to rebuilding the nation's morality.